Molecular Prevalence and Risk Factors for Blastocystis sp. Infection Among School-Aged Children in Makokou and Surrounding Areas, Northeastern Gabon - Thiéry Ndong Mba; Brice Arnaud Pambo-Pambo; Assane Ndiaye; Hilaire Kenguele Moundounga (Zoonoses, 2025)
This study was aimed at assessing the prevalence of infection with Blastocystis , an intestinal protozoan parasite, among school-aged children, and to identify associated risk factors. Although the role of Blastocystis in gastrointestinal symptoms remains debated, it may pose public health concerns, particularly in children with weakened immune systems. A cross-sectional study was conducted between June and October 2024 among children 5–15 years of age in Makokou and surrounding areas of northeastern Gabon. A real-time polymerase chain reaction (PCR) detection kit was used to screen for Blastocystis in stool samples after written informed consent was obtained from the children’s parents or guardians. A total of 389 school-aged children were enrolled in this study. The overall molecular prevalence of Blastocystis sp. infection was 23.43% (95% confidence interval (CI): [0.19–0.28]). Multivariate analysis revealed several factors significantly associated with elevated odds of infection: having a mother with a low education level (adjusted odds ratio [aOR] = 6.39; 95% CI [3.16–12.95], p < 0.001), having a mother who were daily worker (aOR = 2.18; 95% CI [1.17–40.5], p = 0.039), living in rural areas (aOR = 2.65; 95% CI [1.56–4.51], p < 0.001), belonging to a household with a low standard of living (aOR = 1.81; 95% CI [1.5–30.99], p = 0.024), having limited access to safe drinking water (aOR = 6.39; 95% CI [3.16–12.95], p < 0.001), and occasionally consuming poorly washed fruits and vegetables (aOR = 2.82; 95% CI [0.99–8.2], p = 0.046). Blastocystis sp. infection is a major public health issue among children in Gabon, many of whom lack awareness regarding the infection and its transmission routes. Health education initiatives targeting hygiene practices and prevention strategies, particularly those focused on decreasing exposure to water contaminated by domestic animals, are urgently needed.